Innovation In The Evaluation System Of Akidah Akhlak Learning Based On Digital Technology - Suja'i, Ahmad; Abdullah, Jabal Hakim; Hasbullah, Hasbullah; Rustiawan, Hafid (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study examines the innovation of digital technology-based evaluation systems in Akidah Akhlak learning to enhance the effectiveness and efficiency of the assessment process. Evaluation plays a crucial role in ensuring the achievement of learning objectives, including students’ cognitive, affective, and psychomotor aspects. Traditionally, evaluation has been conducted through written or oral tests, but it has now developed with the use of digital applications such as Google Forms, Quizizz, Kahoot, Moodle, and Google Classroom. This innovation aims to present an evaluation system that is more interactive, transparent, and capable of providing immediate feedback to teachers and students. The research method employed is a literature review with a descriptive qualitative approach, analyzing various sources and practices in the implementation of digital evaluation in learning. The findings indicate that the use of digital technology not only facilitates teachers in processing learning outcomes but also increases student motivation and participation. Through interactive quizzes, reflective videos, and online discussions, Akidah Akhlak evaluation can be adapted to students’ needs while simultaneously instilling moral values in a contextual manner. In conclusion, the innovation of digital technology-based evaluation systems supports Akidah Akhlak learning that is more modern and effective in keeping with current developments.